Ajuba LIM Proteins are Negative Regulators of the Hippo Signaling Pathway - Thakur, Meghna Das (2010)
The mammalian Ajuba LIM proteins (Ajuba, LIMD1, WTIP) are cytosolic adapter proteins that exhibit the potential to communicate cell adhesive events with nuclear responses to remodel epithelia [1] [2]. Determining their role(s) in vivo, however, has been challenging due to overlapping tissue expression and functional redundancy. Thus, we turned to Drosophila where a single gene, CG11063 or djub, exists. Drosophila containing djub mutant loss-of-function alleles or depleted of dJub by RNAi identify djub as an essential gene for development and novel regulator of epithelial organ size as a component of the conserved Hippo pathway, which has been implicated in both tissue size control and cancer development [3-5] [6-9]. djub-deficient tissues were small, had decreased cell numbers as a result of increased apoptosis and decreased proliferation, due to downregulation of DIAP1 and cyclin E. This phenocopies tissues deficient for Yorkie (Yki), the downstream target of the Hippo pathway. djub genetically interacts with the Hippo pathway, and epistasis suggests that djub lies downstream of hpo. In mammalian and Drosophila cells, Ajuba LIM proteins/dJub interact with LATS/Wts and WW45/Sav to inhibit phosphorylation of YAP/Yki. This work describes a novel role for the Ajuba LIM proteins as negative regulators of the Hippo signaling pathway.